2022
DOI: 10.3389/fcell.2022.842898
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles: The Landscape in the Progression, Diagnosis, and Treatment of Triple-Negative Breast Cancer

Abstract: Triple-negative breast cancer (TNBC) is a heterogeneous subtype of breast cancer (BC) with diverse biological behavior, high aggressiveness, and poor prognosis. Extracellular vesicles (EVs) are nano-sized membrane-bound vesicles secreted by nearly all cells, and are involved in physiological and pathological processes. EVs deliver multiple functional cargos into the extracellular space, including proteins, lipids, mRNAs, non-coding RNAs (ncRNAs), and DNA fragments. Emerging evidence confirms that EVs enable pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 82 publications
0
14
0
Order By: Relevance
“…Moreover, both breast cancer cells and MSC/ASC-derived EVs are essential for the crosstalk between MSCs/ASCs and breast cancer cells [ 63 , 67 , 68 ]. EVs are a heterogeneous group of membrane-bound vesicles released from cells by invagination and budding.…”
Section: Crosstalk Between Ascs and Breast Cancer Cellsmentioning
confidence: 99%
“…Moreover, both breast cancer cells and MSC/ASC-derived EVs are essential for the crosstalk between MSCs/ASCs and breast cancer cells [ 63 , 67 , 68 ]. EVs are a heterogeneous group of membrane-bound vesicles released from cells by invagination and budding.…”
Section: Crosstalk Between Ascs and Breast Cancer Cellsmentioning
confidence: 99%
“…Recently, growing concentration has been laid on the extracellular vesicles, which are defined as nano-sized membrane-bound vesicles released by almost all cells under physiological and pathological processes ( 33 ). Referring to TNBC, extracellular vesicles were confirmed to deliver functional materials such as proteins, lipids, mRNAs, non-coding RNAs, and DNA fragments into extracellular location and thus play a significant role in shaping tumor microenvironment and in improving the capability of invasion and metastasis of TNBC ( 34 36 ). Our data confirmed higher vesicle-mediated transport activity in TNBC than ACC, which may contribute to elucidate the extreme difference in tumor aggressiveness and prognosis between TNBC and ACC.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was found that sEVs-derived proteins and nucleic acids components enter recipient cells through sEVs uptake pathway and enhanced recipient cells invasion and metastasis by affecting downstream signaling pathways and a series of cascade responses ( 96 ). It was shown that CAFs-derived sEVs carrying miR-181d-5p promoted BC cells invasion and migration by targeting cadal-related homeobox 2 (CDX2) and downregulating CDX2 and its downstream gene -homeobox ( 97 ).…”
Section: Sevs Derived From Breast Cancer and Their Role In Cancer Pro...mentioning
confidence: 99%